Síntese e caracterização de hidrogéis de amido retrogradado e goma gelana utilizados como matriz em sistemas de liberação cólon específica de fármacos - Cardoso, Valéria Maria de Oliveira Cardoso [UNESP] (2014)
Resistant starch exhibits high thermal stability and low solubility. Gellan gum is a natural polysaccharide with important bioadhesive properties. Both polymers can build hydrogels able to control drug release rates. The blending of these natural polysaccharides can improve the physicochemical characteristics of these materials that are often absent in the isolated polymers. Gellan gum/retrograded starch association and crosslinking reaction should promote important modification of properties of these materials such as mechanical strength, swelling and mucoadhesiveness and thus, these strategies can improve the performance of site-specific drug delivery systems. In this study, hydrogels of gellan gum/retrograded starch were used to obtain microparticles by ionotropic gelation or ionic crosslinking (interactions between oppositely charged ions) and dual crosslinking (introducing covalent bonds) methods. The physicochemical characterization of the hydrogels was performed by analysis of profile (hardness, adhesiveness and cohesiveness), rheological properties, morphology and X-ray diffraction. Texture analysis of the behavior was found that higher concentrations of polymer improved the mechanical properties of hydrogels and that the ionic crosslinking improved the hardness and cohesiveness of hydrogels, while the dual crosslinking increased adhesiveness. The set of rheological properties showed that the crosslinking techniques contributed to the elastic character of the systems, and the dual crosslinking originated structures with the most elasticity degree. SEM analysis showed that denser and more packed structures were built in the presence of the ketoprofen. According to the XRD data, the microparticles showed semicrystalline structures and the DR increased the crystallinity. Physicochemical characterization of microparticles was performed by analyzes as moisture content, yield, encapsulation efficiency, size and shape. Ionotropic ...